2018
DOI: 10.1111/1467-8578.12202
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and limitations of the Education, Health and Care plan process from a range of professional and family perspectives

Abstract: The introduction of a new Special Educational Needs and Disability (SEND) Code of Practice in 2015 marked one of the most significant reforms to the SEND statutory assessment process in England since its introduction over 30 years ago. This article presents the findings of a small‐scale study that aimed to identify the extent to which the reforms have successfully addressed some of the shortcomings of the former Statementing process. Interviews, questionnaires and a focus group were used to gain the perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…This concurs with the findings of Curran et al . (2017) and Sales and Vincent (2018). However, the House of Commons Education Committee Report (2019) suggests there is still some way to go in achieving this aim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concurs with the findings of Curran et al . (2017) and Sales and Vincent (2018). However, the House of Commons Education Committee Report (2019) suggests there is still some way to go in achieving this aim.…”
Section: Discussionmentioning
confidence: 99%
“…Other early research (LKMCO, 2015; NAS, 2015; NDCS, 2015 as cited in Curran et al ., 2017) indicates that the impact of the reforms for schools, children and families is mixed. Sales and Vincent (2018) conducted research into how the new EHC plans were working for families and professionals (EHC plans are intended to be more collaborative involving parents/carers and young people in the assessment process and setting outcomes). They concluded that there was greater parental involvement and the approach was more person‐centred.…”
Section: Introductionmentioning
confidence: 99%
“…(FG 1)If a child presents with a specific medical or genetic diagnosis, impacting on their cognitive skills and functioning, it was reported to impact upon the intervention they received. Participants discussed that in certain geographical locations, intervention is only offered to those with a recognized Education, Health and Care Plan (Sales and Vincent, 2018), that is, a legal document provided by UK local government agencies which specifies the provision and intervention required to support the child’s development. Participants talked about taking a holistic approach when considering intervention provision, considering the whole child and how factors such as attention and listening skills or the child’s cognitive ability may impact upon progress in therapy sessions.The priority when you first meet that cleft child, the cleft like characteristics or is it the attention levels, the language levels and which comes first and when are all kind of key.…”
Section: Patient-centered Carementioning
confidence: 99%
“…This is illustrative of how, according to Gramsci, the economy, political society and a part of civil society, the school system in this instance, are inextricably bound together in a constantly shifting relationship of mutual exchange with one another (Jones, 2006). While the process of constructing an EHC plan has been found to empower parents and pupils by placing them at the centre of decisions that affect their own lives (Sales and Vincent, 2018), it is also apparent from Glen's comments that the power and influence of special schools in this respect are limited in that they have no say over how much money is required to support children with SEND.…”
Section: Economic Climate: Budgetary Constraintsmentioning
confidence: 99%